2014
DOI: 10.5055/jom.2014.0238
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based cost analysis of opioid-related nausea and vomiting among inpatients

Abstract: N/V showed to have impact on workload of nurses and (to lesser extent) physicians and economic burden of €31 ± 22 for each N/V episode. In view of these results, the potential costs of strategies to minimize the incidence of N/V (use of antiemetics and/or the use of new analgesics) should be outweighed against the incurred costs of N/V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…In our model, we estimate that the cost of treating an episode of nausea would range between €5 and €12 in the EU5 and between €9 and €20 for an episode of vomiting. These costs are lower than those estimated by Eberhart et al in Germany [ 58 ]. The authors estimated the cost of an episode of nausea and/or vomiting that occurred during or after administration of opioid drug, based on the data from 462 inpatients in 16 German hospitals.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In our model, we estimate that the cost of treating an episode of nausea would range between €5 and €12 in the EU5 and between €9 and €20 for an episode of vomiting. These costs are lower than those estimated by Eberhart et al in Germany [ 58 ]. The authors estimated the cost of an episode of nausea and/or vomiting that occurred during or after administration of opioid drug, based on the data from 462 inpatients in 16 German hospitals.…”
Section: Discussioncontrasting
confidence: 53%
“…The authors estimated the cost of an episode of nausea and/or vomiting that occurred during or after administration of opioid drug, based on the data from 462 inpatients in 16 German hospitals. The costs for an episode of nausea and/or vomiting was estimated as €31±22 when including both the workforce time (€18±14) and materials (€14±13) [ 58 ]. The higher costs in Eberhart et al, compared with our estimates, are partly due to inclusion in Eberhart et al of the costs of material, such as IV lines or gastric tubes, that had to be replaced because of nausea and/or vomiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to minimize the troublesome side effects of opioids to optimize pain management and curtail-associated health care costs suggests a potentially important role for antiemetic co-prescribing. Prophylactic use of antiemetics may improve patient outcomes, including quality of life, and reduce the burden on caregivers, providers, and the health care system [16, 31, 32, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…While there are ample data regarding the economic consequences of nausea and vomiting (NV) in the hospital setting [23, 3235], corresponding data in the outpatient setting are limited. A previous study that examined the costs of gastrointestinal events in outpatients treated with immediate-release (IR) opioids for noncancer pain found that NV was associated with increased all-cause health care utilization and costs over a 3-month follow-up period [31].…”
Section: Introductionmentioning
confidence: 99%